Active Fault Tolerant Control Based on Bond Graph Approach. (9th November 2014) - Allous, Manel; Zanzouri, Nadia
Abstract : This paper proposes a structural fault recoverability analysis using the bond graph (BG) approach. Indeed, this tool enables structural analysis for diagnosis and fault tolerant control (FTC). For the FTC, we propose an approach based on the inverse control using the inverse BG. The fault tolerant control method is also compared with another approach. Finally, simulation results are presented to show the performance of the proposed approach.